2019
DOI: 10.1002/adsc.201901473
|View full text |Cite
|
Sign up to set email alerts
|

Rare‐Earth‐Metal‐Catalyzed Synthesis of Azaindolines and Naphthyridines via C−H Cyclization of Functionalized Pyridines

Abstract: We report herein a rare‐earth‐metal‐catalyzed insertion of a 2‐pyridine C(sp2)−H bond into an intramolecular unactivated vinyl bond. This reaction provides streamlined access to a range of azaindolines in moderate to excellent yields. The salient features of this reaction include simple and mild reaction conditions, 100% atom efficiency, and wide substrate scope. This methodology is also used to construct other nitrogen‐containing compounds such as naphthyridine derivatives. A plausible mechanism for the forma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 70 publications
(6 reference statements)
0
8
0
Order By: Relevance
“…This reaction provides streamlined access to a range of azaindolines 9 in moderate to excellent yields (Scheme 3). [14] Notably, when catalytic amount of dibenzylamine (Bn 2 NH) was added, the yield increased significantly. Mechanism studies have shown the reaction ChemCatChem undergoes an initial C(sp 2 )À H bond activation which followed by C=C insertion to form the final cyclization products.…”
Section: C(sp 2 )à H Alkylationmentioning
confidence: 99%
See 1 more Smart Citation
“…This reaction provides streamlined access to a range of azaindolines 9 in moderate to excellent yields (Scheme 3). [14] Notably, when catalytic amount of dibenzylamine (Bn 2 NH) was added, the yield increased significantly. Mechanism studies have shown the reaction ChemCatChem undergoes an initial C(sp 2 )À H bond activation which followed by C=C insertion to form the final cyclization products.…”
Section: C(sp 2 )à H Alkylationmentioning
confidence: 99%
“…For instance, Chen and coworkers established a highly regio‐ and diastereoselective cyclization reaction of 1,5‐ and 1,6‐dienes ( 36 and 37 ) with anisoles by using a 2‐picoline‐tethered‐half‐sandwich scandium alkyl complex 38 (Scheme 11). [27] The scope of aromatic substrate was also expanded to include tertiary anilines 35 .…”
Section: C−c Bond Formationmentioning
confidence: 99%
“…More recently, Chen and co-workers reported the Ln­[N­(TMS) 2 ] 3 -catalyzed C–H activation/cyclization of functionalized pyridines (Scheme ). Activation of the ortho -pyridyl C–H bond followed by intramolecular coordination and insertion into an unactivated vinylic bond provides facile access to a variety of azaindolines in 23–92% yields.…”
Section: C–c Bond-forming Processesmentioning
confidence: 99%
“…Regarding C–C bond-forming processes, recent reports , of catalytic heteroarene C–H activation using commercially available homoleptic lanthanide amide catalysts are exciting. The commercial availability of these catalysts and their functional group tolerance, paired with the simple and mild reaction conditions, warrant further investigations of scope in organic synthetic methodology.…”
Section: Conclusion and Outlookmentioning
confidence: 99%
See 1 more Smart Citation